Three changes to reduce the loss of dual degree trainees from OMFS national specialty selection in the UK: evidence based proposals. Issue 1 (January 2022) - Al-Najjar, Y.; Rowe, A.; Naredla, P.; Magennis, P.; Smith, A.T.
Abstract: The training pathway for oral and maxillofacial surgery (OMFS) has remained relatively stable for around 30 years. Circumstances surrounding the training pathway have changed including the priorities of individuals considering entering OMFS training. Run-through Specialty Training (ST1) OMFS posts (which include core surgical training) are oversubscribed while direct entry to Specialty Training (ST3) OMFS specialty recruitment rounds have unfilled posts, including places declined by appointable candidates. As part of a project to refine and improve OMFS recruitment and retention, data drawn from the British Association of Oral and Maxillofacial Surgeons (BAOMS) and the OMFS National Selection administering Deanery, Health Education England South West were scrutinised. Numbers of students starting second undergraduate degrees (medicine or dentistry) to pursue an OMFS career are increasing. Of a total of 43 candidates deemed appointable at OMFS ST1 selection but not offered an available post, 16 did not subsequently apply for ST3 selection. In the period studied (2015-20), of a total of 116 unfilled ST3 posts, 39 remained vacant because appointable candidates declined the available posts (33%). Appropriate changes to the current national selection processes could help address the perceived OMFS ST recruitment problems. By increasing the number of available ST1 posts, widening the window during which appointable candidates can continue into training and increasing prior experience recognition (including creating benchmarking processes prior to ST). These three clear, fair and transparent changes could reduce the current levels of attrition.